2017
DOI: 10.2174/0929867324666170518110033
|View full text |Cite
|
Sign up to set email alerts
|

Prothymosin Alpha: An Alarmin and More...

Abstract: We, therefore, suggest that proTα, and likely proTα(100-109), act as alarmins, being important immune mediators as well as biomarkers, and could eventually become targets for new therapeutic/diagnostic approaches in immune-related diseases like cancer, inflammation, and sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 0 publications
3
23
0
Order By: Relevance
“…However, its role still remains elusive. The growing evidences suggested that PTMA being an important immune mediator as well as a biomarker might eventually become a new therapeutic target or diagnostic method in several diseases such as cancer and inflammation [26]. So we focused on the possibility of PTMA as a biomarker of ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…However, its role still remains elusive. The growing evidences suggested that PTMA being an important immune mediator as well as a biomarker might eventually become a new therapeutic target or diagnostic method in several diseases such as cancer and inflammation [26]. So we focused on the possibility of PTMA as a biomarker of ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Parathymosin (PTMS) and prothymosin alpha (PTMA) were more than 4-fold more abundant in cell media from brown adipocytes than white adipocytes ( Figure 2F). These relatively small proteins (11-12 kDa) were quantified with more than five unique peptides in cell media from brown adipocytes (Table S2) and have been shown to be involved in proliferation and regulation of immune function (Hannappel and Huff, 2003;Samara et al, 2017). The biological role of PTMS and PTMA in brown fat has not been explored.…”
Section: Comparative Mapping Of Human Brown Versus White Adipocyte Sementioning
confidence: 99%
“…The developed sandwich-ELISA is currently being applied to specific biological samples, i.e. the supernatants of human cells and cells of cancer cell lines, cultured in the presence of various apoptotic/necroticfactors, in order to verify the literature scenario, according to which human cells may release intact ProTα as a damage-associated molecular pattern (DAMP)/alarmin, under certain survival-threatening circumstances [1]. Potentially, other biological samples, e.g.…”
Section: Experimental/resultsmentioning
confidence: 99%
“…Prothymosin alpha (ProTα) is a highly acidic polypeptide expressed in all mammalian cells and consisting of 109 amino acids in humans. The polypeptide exerts important biological functions acting both intracellularly, as a chromatin-remodeling, proliferation-enhancing and anti-apoptotic factor, and extracellularly, as a pleiotropically-operating immunostimulating mediator [1]. Under certain cellular conditions ProTα may be enzymatically cleaved resulting in biological ly active peptidyl fragments, such as the N-terminal region ProTα (also known as thymosin alpha 1, Tα1) and the C-terminal decapeptide ProTα[100-109].…”
Section: Introductionmentioning
confidence: 99%